Utility of endoscopic ultrasound-guided fine-needle biopsy in the diagnosis of type 1 autoimmune pancreatitis - Oppong, Kofi W.; Maheshwari, Pardeep; Nayar, Manu K.; Darne, Antony; Parkinson, Daniel; Leeds, John S.; Haugk, Beate (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) performs poorly in the histological diagnosis of type 1 autoimmune pancreatitis (AIP). The aim of this study was to assess the performance of fine-needle biopsy (FNB) comparing reverse bevel (RB) and fork-tip (FT) needles.Patients and methods A retrospective study of prospectively maintained databases was performed. Patients with a final diagnosis of type 1 AIP who underwent EUS-FNB during diagnostic workup were included. Pathology reports were reviewed and classified as per international consensus diagnostic criteria (ICDC). The Primary outcome was EUS-FNB sensitivity in diagnosing type 1 AIP.Results Between March 2011 and December 2018, 24 patients with a final diagnosis of type 1 AIP underwent FNB. Six patients underwent biopsy with the RB needle and 18 with the FT needle. Mean age (± SD) 62.2 (± 11.4), 17 (70.8 %) male. No RB samples were diagnostic compared to 14 (78 %) FT; P = 0.001; of which 13 (72 %) were level 1. In eight (44 %) of FT cases a diagnosis was not possible without histology. Initial biopsy was diagnostic in five (62.5 %) of these cases. Including repeat biopsy, seven (87 %) had a diagnosis made by FT needle. Obliterative phlebitis (44 %) was the least frequently identified pathological feature and immunoglobulin (IgG)4 + plasma cells > 10 per high power field (78 %) the most common. Conclusion The FT needle demonstrated good performance for diagnosing type 1 AIP. The results support the preferential use of this core biopsy needle for EUS pancreatic tissue sampling.